On the scheme of delay-waiting direct rapid acquisition of very long PN code - WANG Hao; YI Da-jiang; WANG Fei-xue; ZHUANG Zhao-wen (Tongxin xuebao)
A scheme of direct rapid acquisition of very long PN code that was used in satellite navigation system based on DSSS was presented.In the scheme,the delay of the local PN code was determined through estimate the clock bias between local satellite clock,and which is used to preset the match filter.The scheme was so called “delay-waiting” method.The deeply analysis on technique details and acquisition performance of the scheme is given.